2018
DOI: 10.32677/ejms.2018.v03.i03.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Behaviour of Pharmacy Services Students in Vocational School Of Health Services for Rational Drug Use

Abstract: Objective: To evaluate the knowledge and behaviour of the students about the rational drug use studying in the pharmacy services program in Vocational School of Health Services (VSHS). Methods: This cross-sectional study, conducted between 2017 October and 2018 March, was conducted on the first and second year students of a University VSHS Pharmacy Services Program. In this study, questionnaire was applied to 115 students to assess their knowledge and behaviour about the rational drug use. Results: The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the study conducted by Buyuker and Odabasi [29] to determine the rational drug use levels of 115 pharmacy technician students studying in the Pharmacy Services program, it is stated that students do not have sufficient knowledge about rational drug use.…”
Section: Resultsmentioning
confidence: 99%
“…In the study conducted by Buyuker and Odabasi [29] to determine the rational drug use levels of 115 pharmacy technician students studying in the Pharmacy Services program, it is stated that students do not have sufficient knowledge about rational drug use.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study was conducted by Büyüker SM at Üsküdar University Faculty of Health Sciences in 2020 on rational antibiotic use, and as a result of the study, although most of the participants had enough knowledge about rational antibiotic use (RAU), it was found that the majority of them needed more education on rational drug use (RDU) and RAU and that most of them wanted to treat diseases with alternative treatments (22). Also, Büyüker SM et al ( 2018) studied the effect of the pharmacology education received by the students of the Pharmacy Services Technician program in the same university on their RDU attitudes and found that the students had enough level of knowledge on RDU (23). In a study conducted by Aldwihi Leen A. et al in Saudi Arabia, the use of herbal supplement products before and after the COVID-19 pandemic was investigated, and it was observed that the use of herbal supplements increased significantly during the pandemic process (4).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire is designed by in the light of our previous studies about Rational Drug Use (22,23). In the questionnaire, the students were asked about their age, the department they are studying in, whether they regularly use prescription drugs, whether they use herbal supplements during their illness, whether they use herbal supplements to protect themselves from diseases during the COVID-19 process, who they get support from when they are sick, herbal supplements, and when they are sick.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Openness in religion reflects, in part, a willingness to consider new ideas, as well as to accepting one's values and beliefs. Behavior based on human values can strengthen relationships between two different groups (Buyuker et al, 2018). Silvia (2019) also found that behavior is based on human values in Indonesian religions such as tolerance, no coercion and love of peace can form a harmony community.…”
Section: Discussionmentioning
confidence: 99%